INVESTIGATION INTO THE PERCEPTION OF CONSTRUCTION SUPPLIERS TOWARDS FUTURE ADOPTION OF ELECTRONIC BIDDING FOR PUBLIC PROCUREMENT IN MALDIVES - Afaaf Mohamed Saeed; Dr. Siti Sarah Binti Maidin; Intan Farahana Binti Kamsin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to understand the effort expectancy, performance expectancy, social influence and external factor of government regulation towards the future adoption of electronic bidding for public procurement in the Maldives by using a revised Unified Theory of Acceptance and Use of Technology (UTAUT) model. This research is focused on nationwide construction suppliers of Maldives. The findings of this research identify the most influential determinant towards future adoption of electronic bidding and the relationship between each determinant towards future adoption of electronic bidding.